The strategy, responses and legacy of the first imperialist era in the Sudan 1820-1885 - Ibrahim, Hassan Ahmed (Blackwell Publishing, 2001)
Arab migrations from the north (Egypt) and east (Arabia) into the Eastern Sudan, roughly the present Sudan minus the southern region, started as early as the ninth century and reached their peak in the fourteenth century. Through gradual and peaceful means, the Arabs steadily infiltrated the country, changed its social fabric, and spread their religion and culture among existing Christian and traditional societies.